2018
DOI: 10.7554/elife.37663
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mRNA abundance drive shuttling of RNA binding proteins, linking cytoplasmic RNA degradation to transcription

Abstract: Alterations in global mRNA decay broadly impact multiple stages of gene expression, although signals that connect these processes are incompletely defined. Here, we used tandem mass tag labeling coupled with mass spectrometry to reveal that changing the mRNA decay landscape, as frequently occurs during viral infection, results in subcellular redistribution of RNA binding proteins (RBPs) in human cells. Accelerating Xrn1-dependent mRNA decay through expression of a gammaherpesviral endonuclease drove nuclear tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
147
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(160 citation statements)
references
References 63 publications
13
147
0
Order By: Relevance
“…Consistent with the above analyses, MHV68 infected cells contained less promoter proximal Pol II than uninfected cells, and this signal was partially recovered in the R443I infection ( Fig 1E). This is consistent with data from previous studies that found no defect in serine 2 phosphorylation of elongating Pol II and no consistent change to Pol II elongation during MHV68 infection [23,25]. Notably, the difference in regression line slopes between MHV68 and mock infected cells was more marked when comparing Pol II promoter occupancy, suggesting that the primary transcriptional defect is at the stages of recruitment and initiation.…”
Section: Accelerated Rna Decay Broadly Reduces Pol II Occupancysupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with the above analyses, MHV68 infected cells contained less promoter proximal Pol II than uninfected cells, and this signal was partially recovered in the R443I infection ( Fig 1E). This is consistent with data from previous studies that found no defect in serine 2 phosphorylation of elongating Pol II and no consistent change to Pol II elongation during MHV68 infection [23,25]. Notably, the difference in regression line slopes between MHV68 and mock infected cells was more marked when comparing Pol II promoter occupancy, suggesting that the primary transcriptional defect is at the stages of recruitment and initiation.…”
Section: Accelerated Rna Decay Broadly Reduces Pol II Occupancysupporting
confidence: 92%
“…We previously showed that accelerated mRNA decay by the coordinated activity of muSOX and Xrn1 causes RNA binding protein relocalization from the cytoplasm to the nucleus and that this relocalization plays a role in transcriptional repression in 293T cells [23]. In agreement with our previous findings [23], we observed the expected increase in nuclear levels of the RNA binding proteins PABPC1 and LARP4 in cells infected with WT MHV68 compared to mock or R443I infected cells (Fig 3B). We then multiplexed these TMT labeled fractions and subjected them to quantitative liquid chromatography/tandem mass spectrometry (LC/MS-MS) (Figs 3A and S2A, S1 Table).…”
Section: General Transcription Factors and Pol II Subunits Are Depletsupporting
confidence: 91%
See 3 more Smart Citations